Effects of corn steep liquor supplementation on voluntary selection of tallgrass prairie hay contaminated with sericea lespedeza and uncontaminated tallgrass prairie hay - G.J. Eckerle; L.A. Pacheco; K. C. Olson; John R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2012)
Sericea lespedeza (Lespedeza cuneata) is classified as a noxious weed throughout the Great Plains. It produces copious amounts of seed annually and contains high levels of condensed tannins during much of the growing season, which deters grazing by large domestic herbivores. In Kansas alone, this plant infests approximately 600,000 acres of native range, reducing native grass production by up to 92%. Increased grazing pressure on sericea lespedeza by beef cattle may slow its spread and facilitate some measure of biological control. Feedstuffs or feed additives with tannin-binding properties may promote voluntary consumption of this plant by grazing beef cattle. In previous studies, confined beef cattle fed polyethylene glycol daily ate more sericea lespedeza than cattle that were not fed polyethylene glycol; however, use of polyethylene glycol by commercial beef producers is problematic because feeding it at the rates necessary to increase intake of sericea lespedeza is cost-prohibitive and disallowed from a regulatory standpoint. We reported previously that low to moderate amounts of supplemental corn steep liquor (i.e., 0.6 to 1.8 kg/day) increased intake of tallgrass prairie hay contaminated with sericea lespedeza by beef cows fed in confinement. Corn steep liquor is an inexpensive, palatable, and abundant by-product of wet-corn milling and is generally regarded as safe (GRAS) by the U.S. Food and Drug Administration. Whether beef cattle supplemented with corn steep liquor will readily consume forage contaminated by sericea lespedeza when uncontaminated forage is available simultaneously is unknown. Therefore, the objective of our study was to determine the effects of low-level corn steep liquor supplementation on voluntary selection of tallgrass prairie hay contaminated by sericea lespedeza when uncontaminated tallgrass prairie hay was also available.
Keywords: Cattlemen& #x27; s Day; 2012; Kansas Agricultural Experiment Station contribution; no. 12-231-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1065; Beef Cattle Research; 2012 is known as Cattlemen& #x27; s Day; Beef; Corn steep liquor; Tallgrass prairie hay; Sericea lespedeza; Intake